Association of rs7903146 (IVS3C/T) and rs290487 (IVS3C/T) Polymorphisms in TCF7L2 with Type 2 Diabetes in 9,619 Han Chinese Population - Wang, Jinjin (Public Library of Science, 2013)
AIMS: We aimed to replicate the association of the rs290487 (IVS3C/T) and rs7903146 (IVS3C/T) polymorphisms of transcription factor 7-like 2 (TCF7L2) and type 2 diabetes mellitus (T2DM) in Han Chinese people in Henan province, China. METHODS: In all, 1,842 patients with T2DM and 7,777 normal glucose-tolerant controls underwent genotyping for the T2DM-associated variants rs7903146 (IVS3C/T) and rs290487 (IVS3C/T). W performed a meta-analysis of the association of the risk alleles of rs7903146 (IVS3C/T) and rs290487 (IVS3C/T) in TCF7L2 and T2DM in Han Chinese by combining previous studies with the present study. RESULTS: We found that T2DM was associated with the CC genotype (1.364, 1.137–1.636, p  = 0.001), the recessive model (1.457, 1.156–1.838, p  = 0.001) of rs290487 (IVS3C/T) and haplotype CC (1.116, 1.034–1.204, p  = 0.004) in Han Chinese. Moreover, our meta-analyses supported the association of the T allele (IVS3C/T) of rs7903146 (1.36, 1.24–1.48; p  = 6.404×10(−12)) and T2DM but not the C allele of rs290487 (IVS3C/T) (0.99, 0.85–1.15, p  = 0.890) in Han Chinese. We found no interactions between behavioral risk factors (smoking, alcohol drinking, and physical activity) and rs7903146 (IVS3C/T) and rs290487 (IVS3C/T) polymorphisms. CONCLUSIONS: The CC genotype and the recessive model of the variant rs290487 (IVS3C/T) and CC haplotype of rs7903146 (IVS3C/T) and rs290487 (IVS3C/T) in TCF7L2 may be associated with T2DM in Han Chinese people in Henan province, China.